ECONOMIC VALUATION OF CARBON SAVINGS OF POLOKARTO RUBBER PLANTATIONS, SUKOHARJO - Kusumaningrum, Lia; Candraningtyas, Callista Fabiola; Reza, Anggi Dwiki; Herdananta, Bisma Yoga; Firdausi, Eyda; Alfiyah, Lunetta Khalis; Desai, Astha Dharmashbhai (Universitas Sebelas Maret (UNS), 2026)
Rubber plantations play a significant role in carbon absorption and storage, which can help mitigate the impact of climate change. The importance of rubber plantations can be identified through the economic valuation of carbon stocks. This study aims to calculate the economic value of carbon storage in the Polokarto Rubber Plantation. This research was done at the Polokarto Rubber Plantation, Sukoharjo Regency, Central Java. This study uses the plot method to measure biomass and carbon storage. The estimation of the economic value of carbon is carried out using a proxy market approach, namely, substituting carbon stocks into market prices. The results showed that the total estimated value of carbon storage was 6136.935 tons from 140 hectares of plantation area. The economic valuation of carbon savings in the Polokarto Rubber Plantation shows an economic value of Rp. 2,291,908,029.96. Several recommendations that can be made are to improve plantation management, take a sustainable approach to plantation management to maintain carbon stocks and other environmental benefits, combine satellite technology to monitor changes in carbon stocks in large plantation areas, and establish economic incentive policies for rubber farmers who participate in maintaining carbon stocks through conservation and good land management.